Adolescent Education for Weight Monitoring, Nutritional Status and Physical Activity - Rahayu, Dewi; Idayanti, Idayanti; Paramita, Irma Susan (Sarana Ilmu Indonesia (salnesia), 2025)
Malnutrition and overnutrition are nutritional problems that occur among adolescents in Indonesia. Various factors contribute to these nutritional problems, including limited access to information and low levels of knowledge among adolescents. Lack of knowledge and its implementation in preventing nutritional problems is also experienced in Kampar. Adolescents need to be socialized with the 4 pillars of the Balanced Nutrition Guidelines (PGS) which can be used as guidelines for eating, physical activity, clean living, and maintaining ideal body weight. This community service aimed to form a positive and active attitude to monitor body weight and nutritional status regularly and do physical activity regularly. The activities were carried out in the form of counseling in lectures and discussions using booklet media and adolescent nutritional status assessment tool. Anthropometric measurements were conducted on adolescent boys and girls with a total of 29 people. The counseling resulted in an increase in low physical activity from 48,3% to 58,6%, and monitoring of weight and height from 13,8% to 41,4%. Providing counseling using booklet media and nutritional status discs was considered appropriate to equip adolescents as an effort to increase physical activity and weight monitoring. The participation and initiative of the school (teachers and students) and parents play an important role in achieving the expected results of this counseling.